PEMBERDAYAAN KARANG TARUNA DESA SUNGAI LEBUNG DALAM UPAYA PEMENUHAN KEBUTUHAN BENIH IKAN PATIN DI PEMULUTAN SELATAN KABUPATEN OGAN ILIR - Helmizuryani; Khusnul Khotimah; Harniatun Iswarini; Muhammad Nizar (Altifani Journal: International Journal of Community Engagement, 2024)
Catfish is a popular fish to eat for some people in South Sumatra. The market's strong demand for catfish motivates farmers to keep producing them. One of the strategic stages in enhancing community welfare and attending to local needs is empowering the community, particularly the young of Karang Taruna. In order to create human resources for the production of catfish seeds that promote the sustainability of natural resources, this project aims to transfer science, technology, and skills to Karang Taruna.  Helping with fish seeding, basic bookkeeping, and marketing advice are the strategies employed. Sungai Lebung Village, Pemulutan Selatan District, Ogan Ilir Regency, was the location of the community service project. The outcomes of this community service project can proceed as planned. The efficacy of the catfish spawning aid program is demonstrated by the up to 80% seed survival rate. Additionally, partners have a basic understanding of bookkeeping and marketing for catfish seeding activities.